How to Regenerate Rural Community and Ecoservices: Reversing the Tragedy of the Commons. (1st January 2014) - Francis, C.; Van Wart, J; Johnson, B.
Abstract : Rural areas in the United States are losing people, communities and ecosystem services due to outmigration of population, and loss of small, biodiverse farms. One large driving force is consolidation of farmlands into larger production units and consequent loss of biodiversity in areas within and adjacent to production fields. This century‐long trend has accelerated in the past decade due to high commodity prices and introduction of labor‐saving technologies such as transgenic crops and larger machinery. Federal farm support programs and favorable economic conditions for farm expansion have also contributed to the trend. Research on technologies that are more accessible to large operations and aggressive input marketing practices further stimulate consolidation. In spite of apparent efficiencies and economic power of an industrial agricultural system, all is not positive. There is growing societal concern that current trends are leading to a tragedy of the commons . Issues relating to where and how food is grown, trade‐offs between production of food vs. fuel, and distribution of benefits from agriculture when economic and political power are concentrated are being debated. Growing public interest in food safety, nutrition, food security, and healthy environments adds to discourse about the present structure of agriculture. A growing segment of society envisions national food and farming policies that would help restore small and medium‐sized family farms and rural communities, and to enhance ecosystem services provided by bio‐diverse rural landscapes—in essence, reversing the current tragedy of the commons by pursuing a more equitable and sustainable farming and food system.